(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The purpose of the study: to determine the indicators of readiness of younger schoolchildren for effective mastery of swimming techniques. For this purpose, a survey was conducted of 32 swimming coaches who work with children at the stage of primary education. One of the ways to overcome the problem of adaptation and improve the quality of swimming training for younger schoolchildren is the formation of motor readiness and mastery of swimming skills that precede the study of sports techniques. Motor readiness includes the appropriate level of development of physical qualities as the basis for successful swimming training. The main physical qualities that determine the readiness of children to learn swimming are coordination, flexibility and strength. Endurance allows you to more effectively perform educational tasks in water. Although physical training on land contributes to the overall development of students, the effectiveness of transferring physical qualities in an aquatic environment is limited. It is important to include special exercises in water that will help adapt motor skills to swimming conditions. Swimming coaches confirmed the importance of simulation exercises on land, which contribute to the correct mastery of swimming techniques. The most commonly used exercises are those that simulate body position, arm and leg movements, and exercises with rubber shock absorbers. In general, the formation of readiness of younger schoolchildren to master the swimming technique includes: mastering the breathing technique and the ability to hold it for a long time, forming water-based skills, improving the skills of moving the body in water. The child’s psychological reaction to water is a determining factor in readiness for learning. Students who are afraid of water need an individual approach and special teaching methods. The educational process should be adapted to the individual psychological characteristics of children, which will ensure more effective mastering of swimming techniques.